ISOLATION AND CHARACTERIZATION OF NITRIFYING BACTERIA FROM THE GUT OF EARTHWORM (EISENIA FOETIDA) - S. K. SHAHEEN; K. VIJAYALAKSHMI; K. PAVANA JYOTSNA; N. D. PRASANNA; G. REVATHI; P. JAYALAKSHMI (The Bioscan, 2010)
Atmospheric nitrogen is thought to be a major source of nitrogen in soils. Isolation of nitrifying bacteria from the Earthworm gut (Eisenia foetida) by a microtiter system based on the most probable number (MPN) method has been discussed in this study, with an increased accuracy as compared to standard MPN tube technique. Our studies have shown that there is higher number of nitrifying bacteria associated with earthworm gut and their nitrifying ability was detected through qualitative analysis.